Strategi Penetapan Harga Jual Barang pada UMKM Toko Kelontong dalam Perspektif Ekonomi Syariah (Studi Kasus di Toko Barokah Desa Sembung Kecamatan Wringinanom) - Mochamad Ridwan Adi Wijaya; Fauzan Fauzan (Prodi Ekomoni Syariah STAI Al Akbar Surabaya, 2024)
This study aims to analyse the strategy of setting the selling price at the Grocery Store in Sembung Hamlet, Wringinanom District, Gresik Regency, and review the suitability of the strategy with the principles of Islamic economics. The method used is qualitative research with a case study approach. Data were collected through direct interviews with shop owners and field observations. The results showed that the shop owner applies a cost-based pricing strategy, where the price of goods is determined by adding a profit margin of around 5-10% of the cost of goods. In addition, the shop owner also uses a competitive pricing strategy, adjusting prices with other shops in the neighbourhood to maintain competitiveness. Discounts and special prices are also applied to regular customers or those who buy in large quantities, in order to increase consumer loyalty. Furthermore, from the review of Islamic economics, the pricing in the store is in accordance with the principles of sharia, namely justice ('adl), transparency, and avoiding elements of gharar (uncertainty) and usury. The strategy implemented also reflects the value of ihsan (doing good), where the store does not only pursue profits but also pays attention to consumer welfare, in accordance with maqashid sharia.